2015
DOI: 10.1167/tvst.4.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Porcine Eye Exposure to Primary Blast Insult

Abstract: This computational model offers insights into the mechanisms of ocular injuries arising due to primary blast and may be used to simulate the effects of new protective eyewear designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The activation of these pathways can lead to cell death in experimental models through various molecular mechanisms that depend on the blast intensity and resultant tissue loading 6365. The response to blast exposure may also depend on the physical properties of the tissue6669 and physical properties surrounding the tissue, such as the shape of the face and the use of eye armor in the case of ocular injury 70. It is likely that many of these pathways are downstream of initiating molecular events causing neuronal death and dysfunction, particularly in bTBI that does not result in overt necrosis or vascular damage.…”
mentioning
confidence: 99%
“…The activation of these pathways can lead to cell death in experimental models through various molecular mechanisms that depend on the blast intensity and resultant tissue loading 6365. The response to blast exposure may also depend on the physical properties of the tissue6669 and physical properties surrounding the tissue, such as the shape of the face and the use of eye armor in the case of ocular injury 70. It is likely that many of these pathways are downstream of initiating molecular events causing neuronal death and dysfunction, particularly in bTBI that does not result in overt necrosis or vascular damage.…”
mentioning
confidence: 99%
“…Watson et al reported that areas of maximum stress were found in the thinnest section of the sclera, adjacent to the vitreous base in blast injury simulations using an FEA porcine eye model. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Enucleated porcine eyes were also used for their similarity to humans, especially in the anterior segments ( 11 ). Additionally, a computational model of a porcine eye was used to simulate the effects of the primary blast that was invented for mechanism exploring ( 12 ). However, a rabbit animal model was seldomly used.…”
Section: Introductionmentioning
confidence: 99%